Farm-scale water-energy-food-waste nexus analysis for a closed-loop dairy system - Muell, Jordan D.; Mohtar, Rabi H.; Kan, Eun Sung; Assi, Amjad T.; Pappa, Valentini (Frontiers in Environmental Science, 2022)
Largely due to manure management, intensive livestock production is known to negatively impact air, water, and soil quality. Excessive manure is often applied to soil as fertilizer or stored in lagoon. However, some thermo-chemical methods, such as gasification and pyrolysis, can transform manure from waste into a valuable resource. The closed-loop dairy concept employs these methods to create biochar derived from cow manure for use as a soil amendment and a water filtration medium. This closed-loop concept has the potential to produce syngas and bio-oil for production of electricity, and to reduce excessive nutrients in liquid manure irrigation by filtering manure slurry stored in lagoons. It replaces solid manure with biochar in land applications to further reduce nutrient runoff and increase soil resilience against erosion. In this study, a Water-Energy-Food-Waste nexus-based analysis and resource allocation tool was developed to evaluate the economic, environmental, and social feasibility of the closed-loop dairy system. The tool utilizes several levers to simulate a user-specified dairy operation, such as number of livestock, acres farmed, quantity of effluent irrigation, distribution of manure and biochar products, and type of biomass conversions. Financial estimates from central Texas in 2018 were used to evaluate the profitability of these practices against the costs of a dairy and hay operation. The study showed that the closed-loop dairy system, while case dependent, could be profitable and, based on operational costs, a small dairy of approximately 200 cows could break even. Results also indicate that the benefits of biomass conversions to produce energy byproducts should increase with scale. This study can help many dairy farms that are considering the economic and environmental sustainability of the industry, which has been under scrutiny.